1998
DOI: 10.1176/ajp.155.10.1423
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Agreement Among Psychiatrists in Psychiatric Emergency Assessments

Abstract: Psychiatric emergency service assessments need improvement. This may be accomplished by exploring the underlying structure of psychiatric emergency service concepts, the creation and validation of structured assessment tools, and the creation of practice guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 30 publications
3
41
1
2
Order By: Relevance
“…First, the DSM diagnostic categories that were used had limited reliability. Indeed, an acceptable level of diagnostic reliability in psychiatric emergency departments has been found only for broad diagnostic categories, such as psychosis, depression, and alcoholism (26,27). Given the importance of diagnostic classifications in emergency settings, further research is needed to develop a reliable and valid diagnostic tool for use in these settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the DSM diagnostic categories that were used had limited reliability. Indeed, an acceptable level of diagnostic reliability in psychiatric emergency departments has been found only for broad diagnostic categories, such as psychosis, depression, and alcoholism (26,27). Given the importance of diagnostic classifications in emergency settings, further research is needed to develop a reliable and valid diagnostic tool for use in these settings.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited validity of DSM (25) classification in emergency settings (26,27), diagnostic variables were recoded into more usable categories on the basis of previous research (5,23,28,29). The categories were mental disorders due to a medical condition, psychotic-spectrum disorders, mood disorders, adjustment disorders, neurotic disorders, psychoactive substance use disorders, other conditions that may be a focus of clinical attention, absent or deferred axis I diagnosis, and other diagnoses.…”
Section: Data Collectionmentioning
confidence: 99%
“…The duration of presenting symptoms was calculated and recorded as days. Broad categories for diagnoses were used because of the low validity of diagnoses based on DSM in psychiatric emergency settings (19). In the case of multiple diagnoses, the main diagnosis was used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…However, psychiatrists' assessments and disposition decisions are not an acceptable criterion standard, since previous studies have demonstrated that agreement among psychiatrists regarding assessment of patients in the ED is often poor. 12 This lack of a criterion standard suggests the need for additional studies with patient outcome data to assess the accuracy of these assessments.…”
Section: Limitationsmentioning
confidence: 99%